Conversion of methoxy and hydroxyl functionalities of phenolic monomers over zeolites. Issue 7 (18th December 2015) - Thilakaratne, Rajeeva; Tessonnier, Jean-Philippe; Brown, Robert C.
Abstract : This study investigates the mechanisms for the conversion of methoxy and hydroxyl functionalities in phenolic monomers over zeolites during pyrolysis, identifying bottlenecks for conversion to aromatic hydrocarbons. Abstract : This study investigates the mechanisms of gas phase anisole and phenol conversion over zeolite catalyst. These monomers contain methoxy and hydroxyl groups, the predominant functionalities of the phenolic products of lignin pyrolysis. The proposed reaction mechanisms for anisole and phenol are distinct, with significant differences in product distributions. The anisole mechanism involves methenium ions in the conversion of phenol and alkylating aromatics inside zeolite pores. Phenol converts primarily to benzene and naphthalene via a ring opening reaction promoted by hydroxyl radicals. The phenol mechanism sheds insights on how reactive bi-radicals generated from fragmented phenol aromatic rings (identified as dominant coke precursors) cyclize rapidly to produce polyaromatic hydrocarbons (PAHs). Resulting coke yields were significantly higher for phenol than anisole (56.4% vs. 36.4%) while carbon yields of aromatic hydrocarbons were lower (29.0% vs. 58.4%). Water enhances formation of hydrogen and hydroxyl radicals, thus promoting phenol conversion and product hydrogenation. From this finding we propose phenol–water–zeolite combination to be a high temperature hydrolysis system that can be used to generate both hydrogen and hydroxyl radicals useful for other kinds of reactions.